Optimization of functions with derivatives in an inverted classroom: study through multiple teaching strategies (Práxis Educativa, 2023)
Due to the high percentage of engineering students who fail in mathematics, especially in the first semesters of professional training, a set of didactic strategies for the optimization of functions with derivatives in an inverted classroom was experimented; team work, individual work, work only with videos and work with videos, handouts and presentations were tested. Through the quasi-experimental design with control and experimental groups, it was established the effectiveness of the inverted classroom in the learning of university students and that there are no significant differences in the averages of the exit test when working with different didactic strategies.Keywords: Inverted classroom. Function optimization. Mathematics teaching.